1983
DOI: 10.1055/s-2008-1063091
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Disability on Family Life

Abstract: In the GLC Spina Bifida Survey families were interviewed at 11 years old and the effects of a child with spina bifida on the sibs, father and mother were explored. Health and behaviour of the sibs were reported as at least as good as that of sibs of normal children although mothers of disabled children were more likely to feel that the sibs had suffered. Fathers appeared to have been unrestricted in occupational choice; over the last 9 years 40% had moved upward in social class, twice as many as those who had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
10
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 2 publications
2
10
0
Order By: Relevance
“…Our finding that primary caregivers of children with spina bifida were about twice as likely as other caregivers to report feeling ''blue'' more than a little of the time is consistent with the findings of one previous study (Carr et al 1983). However, a significant difference was not found within the spina bifida group classified by lesion level.…”
Section: Discussionsupporting
confidence: 92%
“…Our finding that primary caregivers of children with spina bifida were about twice as likely as other caregivers to report feeling ''blue'' more than a little of the time is consistent with the findings of one previous study (Carr et al 1983). However, a significant difference was not found within the spina bifida group classified by lesion level.…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, although many studies have addressed the distress of parents of children with hydrocephalus, there is considerable disagreement in the literature with regard to whether or not (and, if so, which) physical and psychosocial variables have any impact on the level of distress of the parents. [3][4][5] To our knowledge, no published study has yet attempted to use standardized and carefully normed questionnaires to assess adjustment after infantile hydrocephalus, or to use multivariate statistical techniques to analyze the data. Such was the purpose of the nresent investigation.…”
mentioning
confidence: 98%
“…Of the remaining 166 articles, a total of 72 articles relating to individuals with an NTD were reviewed. Within these papers, 41 focused on quantitative research [13,19,[23][24][25][26], 15 on qualitative research [9,12,[75][76][77][78][79][80][81][82][83][84][85][86][87][88] and 10 used both quantitative and qualitative methods [22,86,[89][90][91][92][93][94][95][96]. Six review papers were excluded as they did not present original data [28,[97][98][99][100][101].…”
Section: Resultsmentioning
confidence: 99%
“…There were 15 studies that used qualitative methods [9,12,[75][76][77][78][79][80][81][82][83][84][85][86][87][88]. Their findings indicated that SB affected the following aspects of patients' lives: self-image [9], feelings and emotions [75,77], social life [9,22,69,78], acceptance [9], independence [9], impact on school [75,77,85] impact on parents and siblings [9,76,[78][79][80] and concerns about the future [12,80,82,87]. In addition, patients' ability to cope with and adapt to SB has also been well documented.…”
Section: Qualitative Perspectivementioning
confidence: 99%